Gambaran Kualitas Hidup Anak Usia 6-18 Tahun yang Menjalani Kemoterapi di Rumah Sakit Kanker Dharmais, Jakarta Barat - MURDINI UMIATI; WINDY RAKHMAWATI; BANGUN SIMANGUNSONG (Indonesian Journal of Cancer, 2010)
Quality of life is defined as minimal presence of the adverse impact of treatment on the patients perceptions of his or her own functioning. This study is to describe the quality of life among children who received chemotherapy. Twenty two children of age 6 to 18 years of age participated in this study. Data was collected by using the Pediatric Cancer Quality of Life Inventory-32 (PCQL-32) total scale. The result was measured and analyzed by using T score, lower score indicated better quality of life. The most frequent children who received chemotherapy reported high quality of life, 53,3% for 6-12 years and 57,1% for 13-18 years. The result of this study provides information on social functioning which supports interventions for the children who received chemotherapy. The findings indicated the importance for the health worker to provide attention during treatment of the related symptoms, whether physical, psychological or cognitive functioning. Keywords: quality of life, children, chemotherapy